The value of 18F-FDG PET/CT imaging in predicting the efficacy of PD-1/PD-L1 immune checkpoint inhibitors in advanced non-small cell lung cancer - Luo, Huiwen; Li, Linlin; Wang, Jian; Hou, Xuefeng; Li, Xiaofeng; Xu, Wengui; Zhou, Wen; Dai, Dong (Frontiers in Oncology, 2025)
BackgroundWe aimed to investigate the relationship between metabolic parameters based on 18F-FDG PET/CT and the prognosis of programmed cell death protein 1 or its ligand (PD-1/PD-L1) Immune checkpoint inhibitors (ICI) with/without chemotherapy in advanced non-small cell carcinoma (NSCLC).MethodsIn this single-center retrospective study, 115 patients with advanced NSCLC who underwent PD-1/PD-L1 ICI with/without chemotherapy with baseline 18F-FDG PET/CT between 2018 and 2023 were enrolled. Baseline clinical parameters, PD-L1 gene expression, and hematological parameters (including derived neutrophil-to-lymphocyte ratio (dNLR) and lactate dehydrogenase (LDH)) were collected. The optimal cutoff value of PET metabolic parameters was obtained using the receiver operating characteristic (ROC) curve. We used the Chi-square test, binary logistic regression, and cox-regressive analysis to analyze the relationship between the above parameters and clinical outcomes, including disease clinical benefit (DCB), progression-free survival (PFS), and overall survival (OS).ResultsA total of 115 patients were enrolled in the group. After univariate and multivariate analyses, MTVwb [P = 0.002, HR 3.906 (3.644 - 9.279)] and treatment modality [P < 0.001, HR 8.11 (2.51 - 26.21)] were identified as independent prognostic factors for DCB. MTVwb [P = 0.012, HR 2.041 (1.173-3.552)] and treatment modality [P = 0.030, HR 2.045 (1.073 - 3.896)] are independent prognostic factors for PFS, while MTVwb [P =0.013, HR 4.173 (1.356-12.842)] is an independent influencing factor for OS. In the immunotherapy combination group, there was a significant correlation between PD-L1 expression and TLGwb (p=0.029).ConclusionsAmong patients with advanced NSCLC who received PD-1/PD-L1 ICIs in combination or without chemotherapy, MTVwb was an independent influencing factor for DCB, PFS, and OS. The treatment modality is also an independent influencing factor for DCB and PFS. 18F-FDG PET/CT has a very promising application prospect in predicting the prognosis of patients treated with immune checkpoint inhibitors. At the same time, the level of sugar metabolism is positively correlated with PD-L1 expression.